Efeito da hiperglicemia no desenvolvimento do melanoma murino B16F10-Nex2 - Machado, Aline De Oliveira [UNIFESP] (2019)
Epidemiological data indicate that diabetic individuals are at increased risk of developing several types of cancer. Both, Diabetes mellitus (DM) and cancer, are complex, chronic, and potentially fatal diseases that share common risk factors. Hyperglycemia is one of the potential biological mediators that associate these diseases. Recent studies in our group showed a positive correlation between hyperglycemia and in vivo tumor progression of B16F10-Nex2 murine melanoma, and this effect was dependent on infiltrating macrophages, the nitric oxide (NO) synthesized by them, and the participation of the Toll-like receptor 4 (TLR-4) signaling pathway. Therefore, the aim of this work was to evaluate the influence of hyperglycemia on the tumorigenicity of B16F10-Nex2 murine melanoma cells. We also investigated how a hyperglycemic environment modulates the phenotype of bone marrow derived macrophages (BMDMs) and how these findings correlate with the observed effect. B16F10-Nex2 tumor cells were inoculated subcutaneously on normo and hyperglycemic animals, in which hyperglycemia was previously induced by intraperitoneal administration of streptozotocin (STZ), and after 16 days tumor cells were reisolated from the primary tumors for in vitro and in vivo assays. In vitro, tumor cells reisolated from hyperglycemic animals (B16-HG) showed better adaptation (in viability, proliferation and clonogenic assays) and less intracellular accumulation of NO at higher glucose concentrations (60 and 80mM), whereas cells reisolated from normoglycemic animals (B16-NG) showed a better adaptation in lower concentrations of glucose (10 and 30mM). B16-HG cells showed higher production of IL-10 and a pattern suggestive of cytokine consumption, which was not observed by B16-NG cells. High glucose levels did not affect cell migration, and both cells presented similar patterns of induction of pre-angiogenic structures in vitro. In vivo, B16-HG cells were shown to be more aggressive than B16-NG cells in normoglycemic and hyperglycemic animals, which was evidenced in the primary and metastatic tumor models. Taken together, these results suggest that a hyperglycemic environment induced a more aggressive phenotype of murine melanoma cells, and these cells were better adapted to conditions of hyperglycemia. In addition, a hyperglycemic environment, as well as molecules secreted by B16-NG and B16-HG cells were able to influence the in vitro BMDMs phenotype, modulating the synthesis of pro-tumorigenic factors such as NO and pro-and anti-inflammatory cytokines (IL-6 and IL-10, respectively) in the presence or absence of TLR-4 signaling pathway.